Implementasi Mekanisme Keamanan Data dengan Enkripsi Symmetric Key dan Checksum Variable pada Game Online - Darmadi, Herru (Bina Nusantara University, 2013)
This study discusses specifically the encryption mechanism that maintains the integrity of the game data on online games. The purpose of this study is to implement symmetric key encryption and checksum for score calculation. There are two methods conducted in this study: analysis and design. The analysis method isperformed in two ways: analysis of existing systems and analysis of literature study. System design method used is prototyping. The results obtained are implemented on online game competition ‘Expedisi Indosat’ through Facebook from 3 – 30 July 2011. The implementation of symmetric key encryption mechanism and the checksum is useful to maintain data integrity on games especially the results score when the game is running and when there is data transmission from the client to the server.